“EL NADADOR” DE JOHN CHEEVER ENTRE EL PURITANISMO REAL Y LA NATURALEZA FANTÁSTICA=“THE SWIMMER” BY JOHN CHEEVER BETWEEN THE REAL PURITANISM AND THE FANTASTIC NATURE - Rodríguez, Ana Teresa (Cambio Universitario, 2019)
En oposición a su extensa obra anterior a los años 60, John Cheever enfrenta frontalmente en “El nadador” la decadencia sociocultural de los habitantes de los suburbios de la Costa Este. Los topos del viaje y la conquista, así como el constructo esencialmente norteamericano del hombre en sintonía con la naturaleza, presentes en la obra analizada, serán objeto de este análisis con el fin de entender su pertinencia como características fundamentales de la contradictoria cultura mainstream de los Estados Unidos de América. ABSTRACT In contrast to his extensive work prior to the 1960’s, in “The Swimmer” John Cheever confronts head on the sociocultural decay of East Coast suburban inhabitants. The topos of the journey and of the conquest, as well as the essentially North American construct of man in harmony with nature present within the text in question, will be the focus of this analysis, which aims to understand their pertinence as fundamental characteristics of the contradictory mainstream culture of the United States.